Spatial distribution and correlates for catches of Thunnus albacares (Perciformes: Scombridae) and non-target species by the international purse-seine fleet in the Pacific of Costa Rica - Cubero-Pardo, Priscilla (2021)
Introduction: In the Pacific marine ecosystems of Costa Rica, fishing activity by the international purse-seine fleet is important for its wide scope and large impact. Objective: To evaluate the spatial distribution of the catch of yellowfin tuna and non-target species by this fleet, and possible correlates with environmental and fishing variables. Methods: We applied geospatial statistics and multiple regression models to Inter-American Tropical Tuna Commission data, covering from 2002 to 2011. We used a grid the size of the Exclusive Economic Zone (EEZ) with 1 124 cells of 22 x 22 km (unit of analysis), for a total of 11 240 year-cells. Results: The medium tuna (presumably immature for the most part), dolphins, mantas and rays dominated catches within the Thermal Dome (Northeast of the EEZ). Small tuna (all immature), sharks, billfishes, dorado, wahoo, and various small species were caught mostly in the extreme South. Large tuna (mature) was caught specially in the zone center, towards the east of the Submarine Mounts Marine Management Area and the Isla del Coco National Marine Park. Tuna, dorado, dolphins, mantas and rays showed high site fidelity due to their association with geographic and environmental variables, at the time small tuna was associated with sets on floating objects, and big tuna was associated with sets on dolphins. The heterogeneity of non-target species probably hid most correlations. Conclusions: Fishing is affecting the highest trophic levels and an adjusted zoning design is needed to better protect the thermal dome and to take into account susceptibility to the use of purse seines.